Terrorist groups as (economically) rational agents - BAÑARES MARTÍN, Clara (Journal of the Spanish Institute for Strategic Studies, 2023)
The issue of terrorism goes beyond the strictly military, and that is why many of the studies on the topic have focused on the political, social or psychological aspects of the method of terrorism. Some academics have also focused on the financial aspect, researching on the sources and channels of terrorism financing or the costs of their attacks. However, fewer have relied on economic theory for their studies. The possibility of analyzing this issue from economic theory, specifically form microeconomics, sheds light on the decision-making process of terrorist groups, opening up transcendental lines of research for the design of more efficient counterterrorist policies.